Study of Listeners' Expressions in the Presentation of Batak Songs with Special Attention to the Saweran Tradition - Jeremia Pangaribuan; Cahyani Yesika Br Silaban (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to explore the audience's expression during the presentation of Batak songs at Champion Cafe and Lavaz Coffee. The research uses the qualitative research method with a descriptive qualitative approach. Data collection techniques used are observation and interviews. The research is characterized as qualitative with a descriptive design. The result of the study are 1) Expression is a form of self-expression present in each individual, manifesting as physical responses such as body movements when listening to musical melodies. 2) Saweran in the urban society of Medan is an expression involving the giving of money to the music performer when a song presented by the singer or band resonates well with the audience.